Seropositivity of the Rapid Plasma Reagin (RPR) Test in a Dental School Patient Population: a Retrospective Study - James E. Cade, DDS; Charles H. Boozer, DDS, MA; Janet E. Leigh, BDS, DMD (Blackwell Synergy, 2003)
ffie purpose of this retrospective study was to determine the seropositivity of the rapid plasma reagin (RPR) in a dental school patient population.